Profile of patients diagnosed with multiple sclerosis in a city in southern Brazil (Research, Society and Development, 2020)
Multiple Sclerosis (MS) is a chronic disease which leads to demyelination of bundles of central nervous system nerve fibers. Thus, neuronal conduction is no longer saltatory, which results in decreased speed of the nerve impulses. The objective of this research was analyze the profile of MS patients over the past 7 years from 3 care centers located in Cascavel, western Paraná, southern Brazil. This is a descriptive quantitative cross-sectional study with the analysis of medical records of patients in 3 care centers from 2012 to 2018. Data were collected with a questionnaire (script) prepared by the researchers. The information was stored in the SPSS version 20.0 software, obtaining mean, standard deviation, minimum, maximum, interquartile range and absolute and relative frequency values. 24 female and 4 male patients were studied. The sample was diagnosed on average 6.6 years ago. The first reported symptoms were motor / sensory, visual or headache and about 50% were diagnosed within 1 year. The average age of diagnosis was 34.8 years. It was found that 67.9% had been or were under psychological treatment. Regarding the medical treatment for MS, the use of glatiramer acetate, β-interferone 1a and natalizumab has predominated among the patients. Through this study it was found that the majority of people with MS were women, of productive age and with high school education. Regarding the time between the first symptom and the diagnosis, it varied from a few days to 20 years.